Determination of Strategy Planning of Domestic Wastewater Management System in a Commercial Area of Tasikmalaya City - Mila Dirgawati; Mohamad Rangga Sururi; Dhama Yudha Suhendar (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2023)
The domestic wastewater in Cihideung and Tawang Subdistricts as central business district (CBD) areas in Tasikmalaya City is only served by an on-site domestic wastewater management system or Sistem Pengelolaan Air Limbah Domestik Setempat (SPALD-S) which could deteriorate the environment. This study aims to determine the most appropriate type, strategy, and development direction of SPALD based on the existing local conditions for the next 20 years in CBD areas in big cities such as Tasikmalaya. The two methods were used: the multicriteria decision analysis method which refers to the Regulation of the Minister of PUPR Number 04 of 2017, and the Quantitative SWOT analysis method refers to the Guidelines for Preparing a Wastewater Management System Plan. The results of the analysis show that integrated SPALD (SPALD-T) must be implemented aggressively in the two sub-districts based on the key parameters of the existing SPALD conditions, potential for soil contamination, potential danger to air receiving bodies, socio-economic characteristics of the community, public health conditions, education level, financial capability, and the availability of regulations regarding SPALD. The SPALD-T development is suggested to be carried out in stages by determining priority zones for every five years of the planning period.